Comparison of the quality of nimesulide tablets over their shelf life using physical-chemical tests.: Comparison of the quality of nimesulide tablets over their shelf life using physical-chemical tests (Health and Biosciences, 2021)
Nimesulide belongs to the class of non-steroidal anti-inflammatory drugs (NSAIDs). Due to its therapeutic potential, this medication has been used on a large scale in Brazil. Its mechanism of action is associated with the inhibition of cyclooxygenase enzymes, preferably COX-2. The lower affinity for COX-1 reduces the adverse effects that NSAIDs can cause. The use of this medication started in Italy in 1985, but years after its launch, there were cases of hepatotoxicities and liver failure, which in some cases were fatal. To minimize risks and standardize the manufacture of medicines, ANVISA, through the Brazilian Pharmacopoeia, establishes the minimum quality requirements to be followed in order to have quality medicines. To assess the quality of nimesulide tablets, the reference drug, a similar drug and two generic drugs with a recent manufacturing date and close to the expiration date were chosen to monitor possible quality changes. From the results obtained, it was possible to observe that the drug proved to be stable, throughout its validity period in all analyzed samples, with the absence of identification of degradation products by HPLC, or significant change in the quality parameters of the drugs. HPLC was also shown to be adequate in view of the chromatographic performance parameters obtained. However, the dissolved percentage of the drug is changed over time, as evidenced by the dissolution tests and dissolution profile, with a small loss in the dissolution of the drug, which does not compromise the quality of the drugs over the expiration date.
Keywords: nimesulide, quality control, expiration date, stability, storage.